Sarcoma Botryoides of Uterine Cervix in a 16-Year-Old Girl (Journal of Enam Medical College, 2018)
Sarcoma botryoides of uterine cervix is a malignant neoplasm of cervix which accounts 0.2% of all the malignant tumours of the uterus and its peak incidence is between 14−18 years. Here we report a case of a 16-year-old newly married girl who presented with the complaint of vaginal bleeding for one and half months. Histopathology from cervical tissue revealed sarcoma botryoides grade 2, score 5. She was treated by neo-adjuvant chemotherapy and surgery. She was alive for three years from diagnosis and died due to lung metastasis.J Enam Med Col 2018; 8(1): 50-52